RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PEMBAYARAN UANG SEKOLAH BERBASIS CLIENT SERVER - Vivi Kumalasari; Sugiarto Sugiarto; Eni Endaryati (STEKOM PRESS, 2021)
Along with the development of technology, computerized systems are needed in the business world. The computer has a function as a data processing tool that will assist in completing work quickly and precisely. MA Nurul Ulum as an educational institution, especially in the implementation of payment administration activities, still uses a manual or conventional system, so there are still many shortcomings and obstacles that result in a job not being able to run properly. Therefore we need a new system, namely a computer-based payment administration system in order to be able to manage and process payment data quickly, because with computer technology both students and other parties who want to know information related to tuition payments can get it quickly. The purpose of this study is to improve the quality of service to students or parents in making tuition payments. The advantage of the system that will be made is that it provides an administrative information system for paying school fees so that it can make it easier to perform data processing and data retrieval. With an administrative information system that has been integrated in a database, it will facilitate the process of financial calculations and the existence of a Client Server-based school administrative information system will connect between sections, namely the administrative section, school treasurer, principal and head of the foundation making it easier to access financial information. school any time